The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41388-018-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic features of cancer stem cells: the emerging role of lipid metabolism

Abstract: Cancer stem cells (CSCs) are an uncommon subset of tumor cells capable of self-renewal, differentiating, and recreating the parental tumor when transplanted into the murine background. Over the past two decades, efforts toward understanding CSC biology culminated into identifying a set of signaling pathways sustaining "stemness". Nevertheless, while metabolic rewiring is nowadays considered a hallmark of cancer, no consensus has been reached on the metabolic features underlying the plastic nature of CSCs, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 122 publications
(158 reference statements)
4
101
0
Order By: Relevance
“…Since CSCs are very plastic, several studies proposed a glycolytic associated phenotype of CSCs, whereas other findings suggested a prevalent mitochondrial oxidative metabolism (reviewed Concordantly, SCD1 activation and consequent MUFA production seems to be a probable CSC hallmark. 116 Notably, peculiar alterations of CSC-iron trafficking can sustain their role in cancer growth. It has been shown that CSCs of different types of tumours are iron-rich in comparison with tumour cells.…”
Section: Cancer Stem Cell Metabolismmentioning
confidence: 99%
“…Since CSCs are very plastic, several studies proposed a glycolytic associated phenotype of CSCs, whereas other findings suggested a prevalent mitochondrial oxidative metabolism (reviewed Concordantly, SCD1 activation and consequent MUFA production seems to be a probable CSC hallmark. 116 Notably, peculiar alterations of CSC-iron trafficking can sustain their role in cancer growth. It has been shown that CSCs of different types of tumours are iron-rich in comparison with tumour cells.…”
Section: Cancer Stem Cell Metabolismmentioning
confidence: 99%
“…Perturbations in lipid metabolism are emerging as potential drivers and therapeutic targets in cancer development and progression [7]. This is of particular relevance because obesity is a risk factor for a number of cancer types, including multiple myeloma (MM) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the needs of MUFAs for the synthesis of complex lipids such as diacyglycerols (DG), triglycerides (TGs) and cholesterol esters, MUFAs also have important functions in cell signaling and membrane fluidity (11). Therefore, SCD is a highly regulated and conserved enzyme that plays important roles in regulating obesity, insulin resistance, inflammation and cancer progression (12,13). Humans have two SCD isoforms (SCD1 and SCD5), while mouse has four (SCD1-4) that share homology with human SCD1, but not human SCD5 (14,15).…”
Section: Introductionmentioning
confidence: 99%